AuNRs-PPARγmAb Induce Targeted Adipocyte Apoptosis Through Photothermal Effects for Effective Localized Fat Reduction - Hu Y; Xiao K; Chen Z; Ou S; Sima C; Wang H; Zhang J; Zhang Z; Li X (International Journal of Nanomedicine, 2025)
Yiping Hu,1,* Kui Xiao,1,* Ziang Chen,1 Shali Ou,2 Chao Sima,3 Haiyang Wang,4 Jinli Zhang,1 Zhi Zhang,1 Xiaojian Li1 1Department of Burns and Plastic Surgery, Guangzhou Red Cross Hospital, Jinan University, Guangzhou, Guangdong, 510000, People’s Republic of China; 2Department of Oral and Maxillofacial Surgery, Women and Children’s Medical Center Affiliated to Guangzhou Medical University, Guangzhou, Guangdong, 510000, People’s Republic of China; 3Department of Surgery, Shenzhen Guangming District People’s Hospital, Shenzhen, Guangdong, 518107, People’s Republic of China; 4College of Life Sciences, Anhui Normal University, Wuhu, Anhui, 241000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaojian Li, Department of Burns and Plastic Surgery, Guangzhou Red Cross Hospital, Jinan University, 396 Tongfu Road, Guangzhou, 510000, People’s Republic of China, Email lixj64@163.com Zhi Zhang, Department of Burns and Plastic Surgery, Guangzhou Red Cross Hospital, Jinan University, 396 Tongfu Road, Guangzhou, 510000, People’s Republic of China, Email zhangzhicc48@163.comBackground: Non-invasive fat reduction and body contouring technologies have rapidly advanced in plastic surgery. Although various devices have been developed globally for body sculpting, the mechanisms and long-term efficacy of non-surgical fat reduction are still debated. While gold nanorods (AuNRs) have been extensively studied in cancer treatment, their potential in fat reduction has not been explored. This study aims to design a novel nanoplatform combining AuNRs with a PPARγ monoclonal antibody (PPARγmAb) for effective photothermal fat reduction therapy.Methods: AuNRs were chemically activated by adding 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) activator, followed by the addition of PPARγmAb for reaction. Simultaneously, adipose-derived stem cells were induced to differentiate into adipocytes, and an obese mouse model was established. Differentiated adipocytes and obese mice were treated with AuNRs-PPARγmAb and exposed to 808nm near-infrared (NIR) laser irradiation to evaluate fat reduction effects and biocompatibility.Results: The PPARγmAb modification did not significantly affect the optical properties of AuNRs but greatly increased their retention in adipocytes. Compared to AuNRs alone, AuNRs-PPARγmAb showed a stronger photothermal effect on adipocytes under 808 nm near-infrared laser irradiation, inducing cell apoptosis. In obese mice, AuNRs-PPARγmAb treatment significantly reduced adipose tissue weight, size, and thickness, with no major histopathological damage observed in organs. Hematological parameters, as well as liver and kidney function, remained unchanged, confirming the biocompatibility and fat-reducing efficacy of the treatment.Conclusion: AuNRs-PPARγmAb, when exposed to 808nm NIR laser irradiation, effectively targets and induces apoptosis in adipocytes, leading to significant fat reduction. This targeted approach offers a promising method for non-surgical, localized fat reduction. Compared to other fat reduction treatments, it provides the advantages of high specificity, minimal invasiveness, and fewer side effects, highlighting its potential for clinical application.Keywords: obesity, non-surgical fat reduction, gold nanorods, PPARγ, photothermal therapy